Experiments and entrepreneurship in developing countries - Quinn, S; Woodruff, C (Annual Reviews, 2019)
We discuss the value of experiments in illuminating constraints on the growth of firms in developing countries. Experiments have provided insight into both the value and the difficulty of alleviating capital constraints in small firms. They suggest that urban, low-skilled labor markets appear to work reasonably well for firms, although there is a suggestion that frictions in markets for skilled workers may have more effect on firms. While observational data suggest that managerial training is important, experiments have shown that the traditional methods of delivering this training to small enterprises, at least, are not effective. Finally, while most work has focused on alleviating supply constraints, recent experiments have shown that positive demand shocks can be sufficient to generate firm growth. Experiments have been particularly illuminating in uncovering patterns in individual decision making, showing how agents respond to the specific changes in circumstances or incentives generated by the experiment. They are most valuable when they complement insight driven by theory.